Islamic Economic View of the Practice on Partnership Cooperation Agreements - farhan, Muhamad; Wargo, Wargo (Zabags International Journal of Economy, 2024)
This research is field research that examines the Akad Partnership cooperation. The partnership referred to is a business activity broiler chicken farming in the form of collaboration between business partners consists of the People's Inti Company (PIR), namely the company that acts as the core provides raw materials and technical assistance and is responsible in marketing livestock products (eggs or chickens) and breeders as plasma act as manager of chicken cultivation and sell the harvest to the appropriate core by agreement. To carry out this collaboration, Plasma is the chicken farmer provided the conditions proposed by Inti, namely submitting a guarantee in the form of a land certificate. This collaboration explains the price at the beginning of the contract The calculation to Plasma is based on the contract price paid at harvest time to Plasma with calculations of debts for feed, medicines, vaccines along with the seeds given and the rest of the harvest are where Plasma makes a good profit or loss then gives full rights to Inti to market production result. According to the Islamic economic review, cooperation is carried out by Bakul as the core company and Plasma as the people's breeder is permitted in Islam, and is recommended based on the principle of mutual assistance in goodness. As long as the cooperation carried out adheres to principles help each other, need each other and benefit each other. But deep. There is little Islamic economics in the practice of chicken farming. Deviation is a matter of honesty and openness of the collaborating parties.